2019
DOI: 10.1021/acscentsci.8b00955
|View full text |Cite
|
Sign up to set email alerts
|

Chasing Aqueous Biphasic Systems from Simple Salts by Exploring the LiTFSI/LiCl/H2O Phase Diagram

Abstract: Aqueous biphasic systems (ABSs), in which two aqueous phases with different compositions coexist as separate liquids, were first reported more than a century ago with polymer solutions. Recent observations of ABS forming from concentrated mixtures of inorganic salts and ionic liquids raise the fundamental question of how “different” the components of such mixtures should be for a liquid–liquid phase separation to occur. Here we show that even two monovalent salts sharing a common cation (lithium) but with diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 20 publications
0
54
0
Order By: Relevance
“…This indicates more water molecules are bonded to the ions. [40] The reduced hydrogen bonding in ZL-PAAm is further supported by the decrease in storage modulus ( Figure S5, Supporting Information). Furthermore, the OH − produced by the highly hydrated SO 4 2− will interact with H + , thus increasing the relative ratio between H + and OH − and leading to a decrease of the pH value.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…This indicates more water molecules are bonded to the ions. [40] The reduced hydrogen bonding in ZL-PAAm is further supported by the decrease in storage modulus ( Figure S5, Supporting Information). Furthermore, the OH − produced by the highly hydrated SO 4 2− will interact with H + , thus increasing the relative ratio between H + and OH − and leading to a decrease of the pH value.…”
Section: Resultsmentioning
confidence: 82%
“…Moreover, the increase in full width at half-maximum (FWHM) further confirms the reduction of the regularity NH 2 groups ( Figure S4b, Supporting Information), which is ascribed to the circumstance that Li + functions as a "pseudoprotonic acid" dopant that can displace interchain hydrogen bonding. [40] The reduced hydrogen bonding in ZL-PAAm is further supported by the decrease in storage modulus ( Figure S5, Supporting Information). Characteristic peaks of C-C skeletal stretching (middle panel) for three hydrogels all locate at 1105 cm −1 , further confirming the main structure of PAAm is not altered by hydrated ions.…”
Section: Resultsmentioning
confidence: 82%
“…Such systems are potentially of interest for, e.g., recycling applications or membrane‐free flow batteries. [ 59,60 ]…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the electrolyte structures, we suggested that a large size asymmetry between the anions could trigger the formation of aqueous biphasic systems because of packing constraints at the molecular scale. 49 From this, a simple question emerges: how can we define the size of an ion into these solutions and how can it be captured? Moreover, it has been demonstrated that the anion size also modifies the nanostructuration of the electrolytes.…”
Section: Perspectivesmentioning
confidence: 99%